Carrier-free supramolecular nanoassemblies of pure LSD1 inhibitor for effective anti-tumor therapy - Li, Boao; Zhang, Xiangyu; Li, Jibin (Frontiers in Chemistry, 2022)
The LSD1 protein is an oxidase that regulates protein methylation, which regulates gene expression and triggers tumors. Previously, inhibiting LSD1 has been found to be an effective treatment strategy for opposing tumors caused by overexpression of LSD1. Our recent study found that compound 17i was a suitable LSD1 inhibitor with potential anti-tumor activity. However, its extremely insoluble nature limits further validation of its anti-tumor activity at the clinical level. In this study, a unique carrier-free supramolecular nanoassemblies of pure compound 17i is expected to enhance therapeutic efficacy. Aqueous-insoluble compound 17i was mixed with a small quantity of DSPE-PEG2000 into an organic solvent and was prepared as nanoassemblies in water via the one-step nanoprecipitation method. The 17i nanoassemblies have a similar effect on its cytotoxicity when compared with 17i solution in vitro. Importantly, the PEGylated 17i nanoassemblies exhibit significant superiorities over 17i solutions in therapeutic efficiency, anti-tumor immune response and systemic toxicity in BALB/c mice bearing CT-26 colorectal tumors. We envision that the fabrication of pure drug nanoassemblies offers an efficient platform for reforming the undesirable characteristics of drug-like compounds to potentiate the anti-tumor therapeutic effect.